2000
DOI: 10.1128/jb.182.7.1987-1994.2000
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the gerP Locus of Bacillus subtilis and Bacillus cereus Affect Access of Germinants to Their Targets in Spores

Abstract: The gerP1 transposon insertion mutation of Bacillus cereus is responsible for a defect in the germination response of spores to both L-alanine and inosine. The mutant is blocked at an early stage, before loss of heat resistance or release of dipicolinate, and the efficiency of colony formation on nutrient agar from spores is reduced fivefold. The protein profiles of alkaline-extracted spore coats and the spore cortex composition are unchanged in the mutant. Permeabilization of gerP mutant spores by coat extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(102 citation statements)
references
References 25 publications
(10 reference statements)
3
95
0
Order By: Relevance
“…While this role has been appreciated for some time (4), it is only recently that its molecular basis has begun to become understood. For example, in addition to the discovery that the cortex-lytic enzyme CwlJ is in the coat (7), the Moir laboratory has shown that the gerP operon, likely encoding coat protein(s), participates in germination (9). Specifically, that study indicates that the coat does more than merely act as a passive sieve through which germinants flow.…”
Section: Vol 185 2003mentioning
confidence: 99%
“…While this role has been appreciated for some time (4), it is only recently that its molecular basis has begun to become understood. For example, in addition to the discovery that the cortex-lytic enzyme CwlJ is in the coat (7), the Moir laboratory has shown that the gerP operon, likely encoding coat protein(s), participates in germination (9). Specifically, that study indicates that the coat does more than merely act as a passive sieve through which germinants flow.…”
Section: Vol 185 2003mentioning
confidence: 99%
“…On addition of L-alanine or inosine to initiate germination of spores of mutant AM1605, OD was lost more slowly than in wild type, and spores became phase grey, but dipicolinic acid release and loss of heat resistance were equally fast in the wild type and the mutant (data not shown). This is characteristic of spores that have incomplete spore coats, as demonstrated for B. cereus (3). The precise reason for the block is not demonstrated, but such spores could lack the full complement of cortex lytic enzymes, such as the CwlJ protein in B. subtilis, which is extracted during coat removal (1,4,20).…”
Section: Isolation Of Exosporium-defective Spores Of B Cereusmentioning
confidence: 99%
“…A sample was removed for viable counts, and then DPC was added to a 0.025 M concentration and the tubes were incubated at 27°C for 1 h. Sensitivities to 10% n-octanol, 5 and 10% phenol, 10% hydrogen peroxide, and 4% sodium hypochlorite (0.5% available chlorine) were measured as described elsewhere (16,23). Spore germination in L-alanine plus inosine was also done as described elsewhere (5).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to a protective function, the coat has some role in germination (5,6), perhaps by providing access for germinants to the germination proteins located in the inner forespore membrane. A lytic enzyme required for digestion of the spore cortex during germination may also be located in the coat (8,19).…”
mentioning
confidence: 99%